Host and Viral Factors Associated with Hepatitis B Clinical Outcomes in Chronic Infection - Mukasa Kafeero, Hussein; Ocama, Ponsiano; Ndagire, Dorothy; Sendagire, Hakim (International Journal of Pure Medical Research, 2019)
Viral and host factors have been implicated in persistence of HBV infection to chronicity and perhaps to liver cancer. Fortunately 90- 95% of those who get infected in adult hood clear the virus and remain with antibodies suggesting previous exposure to HBV. The underlying reasons as to why majority of the patients with acute infection clear the virus while a small proportion progress to chronic infection lies in the difference in host immunological and genetic factors. The immune determinants of complete clearance are not fully understood but both innate and adaptive are paramount in this response. Similarly, the role of the host genes in the pathogenesis of the virus are not fully elucidated but polymorphisms in genes encoding for the HLA, cytokine and vitamin D receptor (VDR) have been highlighted in in􀃸uencing both disease clearance and progression to chronicity. In this review, the host and viral factors responsible for differential clinical presentation of hepatitis B are discussed. Introduction Hepatitis B virus (HBV) is the causative agent for liver diseases, including chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma (Matsuura, K., Tanaka, Y., Hige, S. et al., 2009). Hepatocellular carcinoma is one of the most common cancers globally with high incidents in Eastern Asia and Sub-Saharan Africa (Jemal, Bray, Center, Ferlay, & Ward, 2011). Most patients who get infected with hepatitis B virus go into an acute phase during when the virus is cleared. None the less, in some patients the virus persists resulting into chronic hepatitis B infection which may later progress to liver cancer. Immune responses and genetic factors of the host along with the viral characteristics remain pivotal in determining the course of the disease Hepatitis B genotypes and subtypes The HBV genome is composed of approximately 3,200 nucleotides (Matsuura et al., 2009). Arauz-Ruiz, Norder, Robertson, & Magnius, (2002) previously classi􀃶ed HBV into 8 genotype identi􀃶ed as A-H based on an intergroup divergence of 8% or more in complete nucleotide sequence whose geographical distributions was previously extensively studied by Sanchez-Tapias, Costa, Mas, Bruguera, & Rodes, (2002) who documented that genotype A is pandemic, B and C are predominant in Asia, D in southern Europe, E in Africa, F in United States of America, G in France while H in Central America. However recent studies by McMahon (2009), Cao (2009), Kurbanov, Tanaka, & Mizokami, (2010) have introduced two new genotypes designated as I and J giving a total of 10 genotypes together with several sub-genotypes. With the exception of the newly identi􀃶ed genotypes, the other genotypes and subgenotypes have well characterized ethnic and geographical distribution
Keywords: hepatitis B; Vitamin D receptor; Hepatitis B virus